Child Data Protection and Commercial Sharenting: A Comparative Legal Analysis of Indonesia and Egypt - Qoneta Masusiyah; Kana Zahra Alma Sayogi; Eksytania Khaila Gisca Nugroho; Shinta Ayu Purnamawati; Muhammad Ahsin Lana (RechtIdee, 2026)
Study Objectives: This article compares Indonesian and Egyptian law to assess how each jurisdiction protects children whose images, identities, locations, emotions, and behavioral traces are disclosed or monetized online.Method/Approach: The study uses normative legal research, including statute, conceptual, and functional comparative approaches.Novelty: It compares Indonesian constitutional guarantees, the Child Protection Law, the Personal Data Protection Law, the Electronic Information and Transactions Law, materials with Egypt’s Personal Data Protection Law No. 151 of 2020 and Executive Regulations No. 816 of 2025, read against the Convention on the Rights of the Child and General Comment No. 25.Findings: The article finds that Indonesia has developed a more explicit child-online-safety framework for electronic-system providers, including age-appropriate design, high privacy settings, risk assessment, and reporting duties. Egypt provides greater operational precision in data processing, notably by treating children’s data as sensitive and requiring explicit,  written consent from a guardian for children under 15. Both systems nevertheless leave a regulatory gap where parental authority, commercial sharenting, and platform monetization are.Conclusion: The article proposes a child-centered compliance model that combines age-sensitive assent, guardian consent, a best-interests assessment for commercial child content, traceable takedown procedures, and platform duties to prevent profiling, amplification, and reuse of high-risk child data.